Genesis of Middle Triassic high-Mg# quartz diorites from the Xiahe area, West Qinling Orogen, Central China, and their geodynamic implications. (January 2021) - Wang, Meng; Pei, Xianzhi; Li, Zuochen; Li, Ruibao; Pei, Lei; Chen, Youxin; Liu, Chengjun; Zhao, Shaowei; Chen, Guochao; Gao, Feng
Graphical abstract: Highlights: The Ren'ai and Daerzang quartz diorites were emplaced at 244−241 Ma. Magma mixing plays dominate role in the generation of the high-Mg# quartz diorites. Flat subduction followed by slab rollback during the early Mesozoic. Abstract: The West Qinling Orogen (WQO) features widespread Triassic granitic rocks, which are crucial to constrain the tectonic evolution of the WQO. Here, we conducted an integrated petrological, geochronological, geochemical, and Sr-Nd-Hf isotope study on quartz diorites and mafic microgranular enclaves (MMEs) from the Ren'ai and Daerzang plutons, Hezuo area, WQO. The quartz diorites and MMEs have crystallization ages between 244 and 241 Ma. The quartz diorites display intermediate SiO2, high Mg# values (62–66) and evolved S-Nd-Hf isotope compositions, indicating an origin from magma mixing process. The MMEs display mineral compositions similar to those of the host rocks, only with more mafic minerals. The The Ren'ai and Daerzang plutons were part of the early Indosinian magmatic belt mainly distributed in the western and middle parts of the northern WQO. In comparison, late Indosinian magmatic rocks are mainly exposed in the eastern WQO. The asymmetric distribution of Early Mesozoic magmatism in the WQO might have been caused by a specific subduction pattern of the A'nimaque-Mianlue oceanic crust. The western and middle WQO experienced a period of flat or low angle subduction in the early stage, followed by slab rollback of the oceanic crust, which accounted for the flare-up of early Indosinian magmatism in the northern WQO. However, the distribution of late Indosinian magmatism might have been caused by asymmetric crustal delamination in the WQO.